Approved Mental Health Professionals and Detention: An Exploration of Professional Differences and Simularities. Issue 2 (15th March 2019) - Stone, Kevin
Abstract : The enactment of the Mental Health Act (MHA) 2007 introduced the role of the multidisciplinary Approved Mental Health Professional (AMHP) in England and Wales by amending The MHA 1983. The role can now be performed by a range of professionals including a psychologist, an occupational-therapist, a social worker or a mental-health/learning difficulties nurse. This amendment amongst other legal provisions replaced the earlier Approved Social Worker role. This is an exploratory qualitative research that aimed to identify if the decision-making relating to management and assessment of risk varied according to the professional background of the AMHP. The decision-making of 10 social work and 10 nursing AMHPs were examined through the use of an experimental vignette containing audio-visual and written materials in order for participants to reach a decision about whether or not to detain. Proposed detention rates between social work and nurse AMHPs were identical although variation was found across the whole sample in terms of the risks that were identified in the vignette. The paper concludes by arguing that these results suggest that differences in the way AMHPs reach decisions may well relate to a variety of individual differences rather than reflecting initial professional identity and training as so often argued in the literature.